IMPACT OF COMMUNICATION SKILLS OF A TEACHER AND ITS ROLE IN THE DEVELOPMENT OF THE STUDENTS ACADEMIC SUCCESS - Prof. SHAMINA SIDDIQUE, (IJRDO - Journal of Business Management, 2025)
Basically, the current study sought to assess the perception of students regarding the role of teacher communication skills in their academics success. Comprehensive questionnaire carrying information including social economic and demographic aspects of the study was designed by the researcher to achieve the set objectives. All those Engineering Colleges of Nagpur. where sports sciences & education programs were offering were taken as population of the study. The empirical data regarding the role of a teacher communication skills in students’ academic success were obtained from (418, thirty percent 30 from each university) samples of 14 Engineering Colleges of Nagpur. The data was collected from the respondents through personally contact and by using the developed scale. After collection of data, the data was finally classified in the form of tables and regression was employed for the analysis of data. After analysis of data the researcher arrived at conclusion that teacher communication skills have significant role in the academic achievement of the students.